Hepatitis B serological markers and plasma DNA concentrations: baseline results from a treatment-monitoring practices trial - Price, Huw; Tamale, Zachary; Chirara, Michael; Hakime, James; Kaleebu, Pontiano; Gilsona, Richard (Aids, 2017)
To examine hepatitis B (HBV) serological markers and plasma DNA concentrations in a large group of untreated HBV/HIV-coinfected individuals in two sub-Saharan settings. Baseline analysis of a randomized controlled trial. DART was a large trial of treatmentmonitoring practices in HIV-infected adults with advanced disease starting antiretroviral therapy at centres in Kampala or Entebbe, Uganda (n¼2317) and Harare, Zimbabwe (n¼999). HBV serological markers [antibody to HBV core antigen, HBV surface antigen (HBsAg), antibody to HBV surface antigen, HBV ‘e’ antigen (HBeAg), and antibody to hepatitis B ‘e’ antigen] and plasma HBV DNA viral load were measured retrospectively on stored baseline samples. Logistic regression was used to examine associations with baseline demographic and clinical factors. The rate of HBsAg positivity was significantly higher in Zimbabwe than Uganda (16.7 vs. 6.1%, adjusted odds ratio¼2.99, P<0.001) despite a similar prevalence of antibody to HBV core antigen (56.3 vs. 52.4%) in the two settings. Overall, HBsAg positivity was associated with male sex (adjusted odds ratio¼1.54, P<0.001) but not with age, WHO disease stage, or CD4þ cell count. HBeAg was detected among 37% of HBsAg-positive patients, with higher rates among those with advanced WHO stage (P¼0.02). Also in HBsAg-positive patients, HBV DNA was undetectable in 21%, detectable but below the level of quantification in 14%, and quantifiable in 65%. A total of 96% of HBeAg-positive and 70% of HBeAg-negative patients had detectable HBV DNA; 92 and 28% of patients, respectively, had HBVDNA viral load more than 2000 IU/ml. Conclusion: High rates of HBV coinfection were observed, highlighting the importance